Chronic kidney disease after 5/6 nephrectomy disturbs the intestinal microbiota and alters intestinal motility. Issue 5 (14th October 2018) - Nishiyama, Kazuhiro; Aono, Kimiya; Fujimoto, Yasuyuki; Kuwamura, Mitsuru; Okada, Toshiya; Tokumoto, Hayato; Izawa, Takeshi; Okano, Ryoichi; Nakajima, Hidemitsu; Takeuchi, Tadayoshi; Azuma, Yasu‐Taka
Abstract: Organ–organ crosstalk is involved in homeostasis. Gastrointestinal symptoms are common in patients with renal failure. The aim of this study was to elucidate the relationship between gastrointestinal motility and gastrointestinal symptoms in chronic kidney disease. We performed studies in C57BL/6 mice with chronic kidney disease after 5/6 nephrectomy. Gastrointestinal motility was evaluated by assessing the ex vivo responses of ileum and distal colon strips to electrical field stimulation. Feces were collected from mice, and the composition of the gut microbiota was analyzed using 16S ribosomal RNA sequencing. Mice with chronic kidney disease after 5/6 nephrectomy showed a decreased amount of stool, and this constipation was correlated with a suppressed contraction response in ileum motility and decreased relaxation response in distal colon motility. Spermine, one of the uremic toxins, inhibited the contraction response in ileum motility, but four types of uremic toxins showed no effect on the relaxation response in distal colon motility. The 5/6 nephrectomy procedure disturbed the balance of the gut microbiota in the mice. The motility dysregulation and constipation were resolved by antibiotic treatments. The expression levels of interleukin 6, tumor necrosis factor‐α, and iNOS in 5/6 nephrectomy mice were increased in the distal colon but not in the ileum. In addition, macrophage infiltration in 5/6 nephrectomy mice was increased in the distal colon but not in the ileum. We found that 5/6 nephrectomy altered gastrointestinal motility and caused constipation by changing the gut microbiota and causing colonic inflammation. These findings indicate that renal failure was remarkably associated with gastrointestinal dysregulation. Abstract : We focused the relation between the kidney and gastrointestinal tract among a number of organ–organ crosstalk is involved in homeostasis. In this study, using generated 5/6 nephrectomy mice, we show chronic kidney disease disturbed the balance of gut microbiota, altered gastrointestinal motilities, and caused constipation.